Content Analysis of Biology Learning Objectives in Merdeka Curriculum: Detection of Misconceptions and Terminological Interference from Predecessor - Eva Nauli Taib; Rostina Taib; Evinopita Taib (Jurnal Penelitian Pendidikan IPA, 2025)
Indonesia's shift from Curriculum 2013 to the Merdeka Curriculum has introduced significant challenges in biology education, particularly in formulating competency-based learning objectives. This study analyzes professional misconceptions in learning objectives using qualitative content analysis of eight curriculum documents—lesson plans and teaching modules—focused on "Environmental Change" from three provinces (Aceh, North Sumatra, Bangka Belitung). Contributors included senior teachers, junior teachers, and pre-service teachers under mentor guidance. Using Webb's curriculum alignment methodology and Bloom's revised taxonomy, we identified three misconception categories. Structural misconceptions showed 75% of documents retained outdated behavioral formats misaligned with competency-based paradigm. Semantic misconceptions demonstrated mean cognitive level drop of 2.1 levels from expected C6 to observed C1–C3 objectives. Pragmatic misconceptions revealed 62.5% used low-validity, recall-based assessments. These consistent patterns across regions and teacher experience levels suggest systemic rather than contextual issues. Professional misconceptions mirror student cognition patterns, characterized by structural coherence and resistance to surface-level correction. Addressing these requires explicit conceptual change strategies, not mere technical training. This study offers a research-based framework to inform interventions for effective competency-based biology instruction adoption.